A Feasibility Study on PV Solar Home System - Banquillo, Elna A. (College of Engineering, 1996)
The Solar Panel Assembly Corporation is a pioneer assembly plant of photovoltaic panels which aims to electrify off-grid rural households in the Philippines. This project will be primarily headed by Philippines National Oil Companies (PNOC), and supported by government agencies and private sectors as well. In coordination with the University of the Philippines Solar Laboratory. A feasibility study on the project was conducted. A market study was done to evaluate the current demand and supply of electricity in the country and the analyses show that there exists a significant supply-demand gap. The company aims to capture 5.5% of this total potential market. Thus, this proves the project to be feasible in the market. The technical study also reveals to be feasible. However, with the introduction of the new technology which is basically from abroad, a few difficulties in the first years of operations are to be expected. The plant will be located in University of the Philippines, Diliman, with a target production of 84,480 panels per year. Financially, the project is also feasible. With the capitalization coming from Philippine National Oil Companies (PNOC), together with the support from the Department of Energy Renewable Energy Power Program (DOE-REPP) and private creditors, financing the project is not such a problem. The social beneficiaries, on the other hand, primarily include the Filipino people, most especially the rural communities who will be electrified with solar home systems. With the generation of employment and income, government taxes, and local materials demand, employees, rural school children, Philippine government, and local suppliers will likewise benefit the project. The organization is going to be a corporation with PNOC as its initial owner. In the future, ownership will then be distributed to interested parties and investors. The plant organization is composed of a general manager and the supporting bodies of the production. With the current unemployment rate in the country, the organizational construction of SPAC is practically feasible. Hence based on this feasible study, it only proves that the Solar Panel Assembly Corporation is indeed a promising project to push through.